Atomic cation-vacancy engineering of two-dimensional nanosheets for energy-related applications. (6th February 2023) - Liu, Chao; Liu, Yifan; Ma, Renzhi; Sasaki, Takayoshi; Wang, Xin; Xiong, Pan; Zhu, Junwu
Abstract : This review focuses on the synthetic strategies and characterization methods of atomic cation vacancies in 2D nanosheets and their energy-related applications. Abstract : Two-dimensional (2D) nanosheets delaminated from their layered parent crystals have shown great promise in energy-related applications, owing to their unique 2D features with atomic thickness, large specific surface area and tunable electronic properties. However, the performance of pristine 2D nanosheets is still insufficient for their further applications. Cation-vacancy engineering of 2D nanosheets is one of the most straightforward and effective approaches to improve their performance. Herein, the recent research progress in atomic cation-vacancy engineering of 2D nanosheets is reviewed, including layered transition metal oxide nanosheets, transition metal dichalcogenide nanosheets, layered double hydroxide nanosheets, transition metal carbide and nitride nanosheets, graphene, boron nitride and carbon nitride nanosheets. Various facile strategies are introduced for the incorporation of atomic-scale cation vacancies within these 2D nanosheets. The resulting superior electrochemical performances of these cation-deficient 2D nanosheets are discussed in detail for some typical energy-related applications, such as metal ion batteries, lithium–sulfur batteries, electrocatalysis and photocatalysis. Finally, the challenges and perspectives are outlined for future research.